Goya dans l’historiographie française du xixe siècle : images et textes - Agnès Gué (Les Cahiers de l'École du Louvre)
During the first half on the nineteenth century, France developed an interest in Spanish art. Francisco Goya y Lucientes (1746–1828) gradually made a name for himself, especially for his print cycle Los Caprichos, and was often considered the Spanish artist par excellence. In the second half of the century, many books – sometimes illustrated – about the artist began to appear. While art historians and critics were fascinated by Goya, he was not as highly regarded as Velázquez. However, after the major retrospective organized in Madrid in May 1900, Goya was progressively rehabilitated and recognized. This evolution in the way the artist was regarded may be linked to his historiography, in which the importance of the reproductions of his works – whose number increased, thus providing access to numerous works in Spanish collections – should not be neglected. During the first half on the nineteenth century, France developed an interest in Spanish art. Francisco Goya y Lucientes (1746–1828) gradually made a name for himself, especially for his print cycle Los Caprichos, and was often considered the Spanish artist par excellence. In the second half of the century, many books – sometimes illustrated – about the artist began to appear. While art historians and critics were fascinated by Goya, he was not as highly regarded as Velázquez. However, after the major retrospective organized in Madrid in May 1900, Goya was progressively rehabilitated and recognized. This evolution in the way the artist was regarded may be linked to his historiography, in which the importance of the reproductions of his works – whose number increased, thus providing access to numerous works in Spanish collections – should not be neglected.